Empire of the Senses: The Sensual Culture Reader - Howes, David (Oxford Berg, 2005)
In Empire of the Senses the senses are considered as cultural systems. Bringing together classic pieces by key thinkers--from Marshall McLuhan and Alain Corbin to Susan Stewart and Oliver Sacks--as well as newly commissioned articles, this path-breaking book provides a comprehensive overview of the "sensual revolution," where all manner of disciplines converge. Its aim is to enhance our understanding of the role of the senses in history and across cultures by overturning the hegemony of vision in contemporary theory and demonstrating that all senses play a role in mediating cultural experience. It asks provocative questions that most of us take for granted. Are there, for example, only five senses, or is this assumption a Western construct? This radical contribution to revisioning cultural studies will be essential reading for anyone hoping to understand the full complexity of how we experience our world.